Doctor-patient relationship: Islamic perspective - Chamsi-Pasha, Hassan (Saudi Med J, 2016)
The doctor-patient relationship is an intricate concept in which patients voluntarily approach a doctor and become part of a contract by which they tend to abide by doctor’s instructions. Over recent decades, this relationship has changed dramatically due to privatization and commercialization of the health sector. A review of the relevant literature in the database of MEDLINE published in English between 1966 and August 2015 was performed with the following keywords: doctor-patient relationship, physician-patient relationship, ethics, and Islam. The Muslim doctor should be familiar with the Islamic teachings on the daily issues faced in his/her practice and the relationship with his/her patients.